Size Effect and Fracture Toughness of Glass Fiber Composite Structures - Hamza Alharthi, Mohammed Y. Abdellah, Hany S. Abdo, Mohamed K. Hassan (International Journal of Advanced Science and Technology, 2020)
The size effect is referred to as a decrease in nominal strength respect to the dimension of the structure, this effect is widely observed in Quasi-brittle material such as; reinforced epoxy laminates. This work aims to study the change of mechanical properties of the composite structures due to the size effect resulting in the existing hole. Moreover, the effect of inserting a few layers of steel mesh is investigated. Therefore, two types of composite laminate are manufactured by hand layup techniques. One of the laminates consists of eight layers from woven glass fibers (S1) and the second one consists of a mix of four layers from woven glass fibres and four steel network mats (S2) connected. Open holes specimens of these materials with (2, 4, 6, 8, 10, and 12) mm diameter are used under tensile test, also tension test is performed on the un-notch sample to obtain necessary mechanical characteristic for comparison. The fracture toughness, which is a dominated parameter in all fields of fracture and failure behaviors of composite structure, is measured using a simple center crack notch specimen. The results showed that the S2 specimen gives lower strength and fracture toughness than S1, whereas, S2 has little size affect nearly 45% reduction while S1 gives 86 %. Besides, inserting enhanced damage tolerance by increasing ductility while decrease both fracture toughness and tensile strength. Moreover, the steel mesh decreases the size effect of a composite laminated plate with a circular open hole.